Hotels in Łódź city space - Włodarczyk, Bogdan (Turyzm/Tourism, 2015)
The article is an attempt to describe the current development level of the hotel base in Łódź – the third largest city in Poland. The analysis deals with both historical and spatial aspects. The detailed analysis of the hotel distribution in Łódź is based on A. KOWALCZYK’s (2001a) categorisation of hotel location types in urban areas. The Łódź hotel base is compared with other large cities in Poland.